Within and Between Panel Cointegration in the German Regional Output-Trade-FDI Nexus - Timo Mitze (European Regional Science Association (ERSA), 2011)
For spatial data with a sufficiently long time dimension, the concept of global cointegration has been recently included in the econometrics research agenda. Global cointegration arises when non-stationary time series are cointegrated both within and between spatial units. In this paper, we analyze the role of globally cointegrated variable relationships using German regional data (NUTS 1 level) for GDP, trade, and FDI activity during the period 1976-2005. Applying various homogeneous and heterogeneous panel data estimators to a Spatial Panel Error Correction Model (SpECM) for regional output growth allows us to analyze the short- and long-run impacts of internationalization activities. For the long-run cointegration equation, the empirical results support the hypothesis of export- and FDI-led growth. We also show that for export and outward FDI activity positive cross-regional effects are at work. Likewise, in the short-run SpECM specification, direct and indirect spatial externalities are found to be present. As a sensitivity analysis, we use a spatial weighting matrix based on interregional goods transport flows rather than geographical distances. This scheme thus allows us to address more soundly the role of positive and negative effects of trade/FDI on output activity for a system of interconnected regions.
Keywords: 330